Pretreatment dengan Phanerochaete chrysosporium dalam Hidrolisis Asam Encer Sludge Kertas - Elis Nina Herliyana; Ai Rosah Aisah; Isroi Isroi (Jurnal Silvikultur Tropika, 2011)
Pretreatment with Phanerochaete chrysosporium in Paper Sludge  Dilute Acid HidrolisisFungi Phanerochaete chrysosporium is one of Basidiomycetes, which is able to degrade lignocelluloses materials, such as paper sludge. The cellulose from paper sludge could been as bioethanol raw materials, so there is need a delignification process in order to remove lignin. The delignification process could be performed by utilizing fungi P. chrysosporium as lignin degrading agent. In this work, duration of incubation (6 days, 12 days and control) and acid concentration (2.5 %, 5 % and control) factors were used to determine the reducing sugar content of paper sludge. The contents of cellulose and hemicelluloses exhibited increase as compared with those of control namely between 3.5-4.5% and 0.4-1.7% respectively, whereas kappa number exhibited decrease as compared to control namely between 10.2-15%. The enzyme activities of LiP, MnP and cellulase of 6 days incubation as much as 0.789 and 0.062, and 0 U/ml, whereas those of 12 days incubation as much as 0, 0.069 and 0.165 U/ml. The reducing sugar produced was still relatively low, namely between 0.3x10-2-2.6 g/l.  Factor of acid concentration gave significant effect on reducing sugar produced, and on the basis of Duncan advanced test, each level of the acid concentration differed significantly from each other.